Hadith #6724 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
The commencement of the Divine Inspiration to Allah’s Messenger (ﷺ) was in the form of good righteous (true) dreams in his sleep. He never had a dream but that it came true like bright day light. He used to go in seclusion (the cave of) Hira where he used to worship(Allah Alone) continuously for many (days) nights. He used to take with him the journey food for that (stay) and then come back to (his wife) Khadija to take his food like-wise again for another period to stay, till suddenly the T
Grade: Sahih

Hadith #6725 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “A good dream (that comes true) of a righteous man is one of forty-six parts of prophetism.”
Grade: Sahih

Hadith #6726 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
The Prophet (ﷺ) said, “A true good dream is from Allah, and a bad dream is from Satan.”
Grade: Sahih

Hadith #6727 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ﷺ) said, “If anyone of you sees a dream that he likes, then it is from Allah, and he should thank Allah for it and narrate it to others; but if he sees something else, i.e., a dream that he dislikes, then it is from Satan, and he should seek refuge with Allah from its evil, and he should not mention it to anybody, for it will not harm him.”
Grade: Sahih

Hadith #6728 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
The Prophet (ﷺ) said, “A good dream that comes true is from Allah, and a bad dream is from Satan, so if anyone of you sees a bad dream, he should seek refuge with Allah from Satan and should spit on the left, for the bad dream will not harm him.”
Grade: Sahih

Hadith #6729 - Sahih al-Bukhari - Ubada bin As-Samit (Sahih al-Bukhari)
The Prophet (ﷺ) said, “The (good) dreams of a faithful believer is a part of the forty-six parts of prophetism:’
Grade: Sahih

Hadith #6730 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “The (good) dream of a faithful believer is a part of the forty-six parts of prophetism.”
Grade: Sahih

Hadith #6731 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “A good dream is a part of the forty six parts of prophetism.”
Grade: Sahih

Hadith #6732 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “Nothing is left of the prophetism except Al-Mubashshirat.” They asked, “What are Al-Mubashshirat?” He replied, “The true good dreams (that conveys glad tidings).
Grade: Sahih

Hadith #6733 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Some people were shown the Night of Qadr as being in the last seven days (of the month of Ramadan). The Prophet (ﷺ) said, “Seek it in the last seven days (of Ramadan).
Grade: Sahih

Hadith #6734 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “If I stayed in prison as long as Joseph stayed and then the messenger came, I would respond to his call (to go out of the prison) .”
Grade: Sahih

Hadith #6735 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard the Prophet (ﷺ) saying, “Whoever sees me in a dream will see me in his wakefulness, and Satan cannot imitate me in shape.” Abu `Abdullah said, “Ibn Seereen said, ‘Only if he sees the Prophet (ﷺ) in his (real) shape.'”
Grade: Sahih

Hadith #6736 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Whoever has seen me in a dream, then no doubt, he has seen me, for Satan cannot imitate my shape.
Grade: Sahih

Hadith #6737 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
The Prophet (ﷺ) said, “A good dream is from Allah, and a bad dream is from Satan. So whoever has seen (in a dream) something he dislikes, then he should spit without saliva, thrice on his left and seek refuge with Allah from Satan, for it will not harm him, and Satan cannot appear in my shape.”
Grade: Sahih

Hadith #6738 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Whoever sees me (in a dream) then he indeed has seen the truth .”
Grade: Sahih

Hadith #6739 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Who ever sees me (in a dream) then he indeed has seen the truth, as Satan cannot appear in my shape.”
Grade: Sahih

Hadith #6740 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I have been given the keys of eloquent speech and given victory with awe (cast into the hearts of the enemy), and while I was sleeping last night, the keys of the treasures of the earth were brought to me till they were put in my hand.” Abu Huraira added: Allah’s Messenger (ﷺ) left (this world) and now you people are carrying those treasures from place to place.
Grade: Sahih

Hadith #6741 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “I saw myself (in a dream) near the Ka`ba last night, and I saw a man with whitish red complexion, the best you may see amongst men of that complexion having long hair reaching his earlobes which was the best hair of its sort, and he had combed his hair and water was dropping from it, and he was performing the Tawaf around the Ka`ba while he was leaning on two men or on the shoulders of two men. I asked, ‘Who is this man?’ Somebody replied, ‘(He is) Messia
Grade: Sahih

Hadith #6742 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
About a man who came to Allah’s Messenger (ﷺ) and said, “I was shown in a dream last night…” Then Ibn `Abbas mentioned the narration.
Grade: Sahih

Hadith #6743 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) used to visit Um Haram bint Milhan she was the wife of ‘Ubada bin As-Samit. One day the Prophet (ﷺ) visited her and she provided him with food and started looking for lice in his head. Then Allah’s Messenger (ﷺ) slept and afterwards woke up smiling. Um Haram asked, “What makes you smile, O Allah’s Messenger (ﷺ)?” He said, “Some of my followers were presented before me in my dream as fighters in Allah’s Cause, sailing in the middle of the seas like ki
Grade: Sahih

Hadith #6744 - Sahih al-Bukhari - Kharija ibn Zayd ibn Thabit خارجة بن زيد بن ثابت الأنصاري (Sahih al-Bukhari)
Um Al-`Ala an Ansari woman who had given a pledge of allegiance to Allah’s Messenger (ﷺ) told me:, “The Muhajirln (emigrants) were distributed amongst us by drawing lots, and we got `Uthman bin Maz’un in our share. We made him stay with us in our house. Then he suffered from a disease which proved fatal. When he died and was given a bath and was shrouded in his clothes. Allah’s Messenger (ﷺ) came, I said, (addressing the dead body), ‘O Aba As-Sa’ib! May Allah be Merciful to you!
Grade: Sahih

Hadith #6745 - Sahih al-Bukhari - Az-Zuhri from Malik bin Aus (Sahih al-Bukhari)
Regarding the above narration, The Prophet (ﷺ) said, “I do not know what Allah will do to him (Uthman bin Maz’un).” Um Al-`Ala said, “I felt very sorry for that, and then I slept and saw in a dream a flowing spring for `Uthman bin Maz’un, and told Allah’s Messenger (ﷺ) of that, and he said, “That flowing spring symbolizes his good deeds.”
Grade: Sahih

Hadith #6746 - Sahih al-Bukhari - Abu Qatada ibn Rab'i (Sahih al-Bukhari)
(a companion of the Prophet (ﷺ) and one of his cavalry men) “I heard Allah’s Messenger (ﷺ) saying, “A good dream is from Allah, and a bad dream is from Satan; so, if anyone of you had a bad dream which he disliked, then he should spit on his left and seek refuge with Allah from it, for it will not harm him.”
Grade: Sahih

Hadith #6747 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “While I was sleeping, I was given a bowl full of milk (in a dream), and I drank of it to my fill until I noticed its wetness coming out of my nails, and then I gave the rest of it to `Umar.” They (the people) asked, “What have you interpreted (about the dream)? O Allah’s Apostle?” He said, “(It is Religious) knowledge.”
Grade: Sahih

Hadith #6748 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “While I was sleeping, I was given a bowl full of milk (in the dream) and I drank from it (to my fill) till I noticed its wetness coming out of my limbs. Then I gave the rest of it to `Umar bin Al-Khattab.” The persons sitting around him, asked, “What have you interpreted (about the dream) O Allah’s Messenger (ﷺ)?” He said, “(It is religious) knowledge.”
Grade: Sahih

Hadith #6749 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “While I was sleeping, some people were displayed before me (in a dream). They were wearing shirts, some of which were merely covering their breasts, and some a bit longer. Then there passed before me, `Umar bin Al-Khattab wearing a shirt he was dragging it (on the ground behind him.)” They (the people) asked, “What have you interpreted (about the dream) O Allah’s Apostle?” He said, “The Religion.”
Grade: Sahih

Hadith #6750 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “While I was sleeping, I saw (in a dream) the people being displayed before me, wearing shirts, some of which (were so short that it) reached as far as their breasts and some reached below that. Then `Umar bin Al-Khattab was shown to me and he was wearing a shirt which he was dragging (behind him).” They asked. What have you interpreted (about the dream)? O Allah’s Messenger (ﷺ)?” He said, “The religion.”
Grade: Sahih

Hadith #6751 - Sahih al-Bukhari - Qais bin Ubad (Sahih al-Bukhari)
I was sitting in a gathering in which there was Sa`d bin Malik and Ibn `Umar. `Abdullah bin Salam passed in front of them and they said, “This man is from the people of Paradise.” I said to `Abdullah bin Salam, “They said so-and-so.” He replied, “Subhan Allah! They ought not to have said things of which they have no knowledge, but I saw (in a dream) that a post was fixed in a green garden. At the top of the post there was a handhold and below it there was a servant. I was asked to clim
Grade: Sahih

Hadith #6752 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said (to me), “You were shown to me twice in (my) dream. Behold, a man was carrying you in a silken piece of cloth and said to me, “She is your wife, so uncover her,’ and behold, it was you. I would then say (to myself), ‘If this is from Allah, then it must happen.’ “
Grade: Sahih

Hadith #6753 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said to me, “You were shown to me twice (in my dream) before I married you. I saw an angel carrying you in a silken piece of cloth, and I said to him, ‘Uncover (her),’ and behold, it was you. I said (to myself), ‘If this is from Allah, then it must happen.’ Then you were shown to me, the angel carrying you in a silken piece of cloth, and I said (to him), ‘Uncover (her), and behold, it was you. I said (to myself), ‘If this is from Allah, then it must happen
Grade: Sahih

Hadith #6754 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “I have been sent with Jawami al-Kalim (i.e., the shortest expression carrying the widest meanings), and I was made victorious with awe (cast into the hearts of the enemy), and while I was sleeping, the keys of the treasures of the earth were brought to me and were put in my hand.” Muhammad said, Jawami’-al-Kalim means that Allah expresses in one or two statements or thereabouts the numerous matters that used to be written in the books revealed bef
Grade: Sahih

Hadith #6755 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
(In a dream) I saw myself in a garden, and there was a pillar in the middle of the garden, and there was a handhold at the top of the pillar. I was asked to climb it. I said, “I cannot.” Then a servant came and lifted up my clothes and I climbed (the pillar), and then got hold of the handhold, and I woke up while still holding it. I narrated that to the Prophet (ﷺ) who said, “The garden symbolizes the garden of Islam, and the handhold is the firm Islamic handhold which indicates that you
Grade: Sahih

Hadith #6756 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I saw in a dream a piece of silken cloth in my hand, and in whatever direction in Paradise I waved it, it flew, carrying me there. I narrated this (dream) to (my sister) Hafsa and she told it to the Prophet (ﷺ) who said, (to Hafsa), “Indeed, your brother is a righteous man,” or, “Indeed, `Abdullah is a righteous man.”
Grade: Sahih

Hadith #6757 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “When the Day of Resurrection approaches, the dreams of a believer will hardly fail to come true, and a dream of a believer is one of forty-six parts of prophetism, and whatever belongs to prothetism can never be false.” Muhammad bin Seereen said, “But I say this.” He said, “It used to be said, ‘There are three types of dreams: The reflection of one’s thoughts and experiences one has during wakefulness, what is suggested by Satan to frighten the drea
Grade: Sahih

Hadith #6758 - Sahih al-Bukhari - Kharija ibn Zayd ibn Thabit خارجة بن زيد بن ثابت الأنصاري (Sahih al-Bukhari)
Um Al-`Ala an Ansari woman who had given the Pledge of allegiance to Allah’s Messenger (ﷺ) said, “`Uthman bin Maz’un came in our share when the Ansars drew lots to distribute the emigrants (to dwell) among themselves, He became sick and we looked after (nursed) him till he died. Then we shrouded him in his clothes. Allah’s Messenger (ﷺ) came to us, I (addressing the dead body) said, “May Allah’s Mercy be on you, O Aba As-Sa’ib! I testify that Allah has honored you.” The Proph
Grade: Sahih

Hadith #6759 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “(I saw in a dream that) while I was standing at a well and drawing water therefrom, suddenly Abu Bakr and `Umar came to me. Abu Bakr took the bucket and drew one or two buckets (full of water), but there was weakness in his pulling, but Allah forgave him. Then Ibn Al- Khattab took the bucket from Abu Bakr’s hand and the bucket turned into a very large one in his hand. I have never seen any strong man among the people doing such a hard job as `Umar did, till (
Grade: Sahih

Hadith #6760 - Sahih al-Bukhari - Salim's father (Sahih al-Bukhari)
about the Prophet’s dream in which he has seen Abu Bakr and `Umar: The Prophet (ﷺ) said, “I saw (in a dream) that the people had gathered. Then Abu Bakr stood up and pulled out one or two buckets full of water (from a well) and there was weakness in his pulling — may Allah forgive him. Then Ibn Al- Khattab stood up, and the bucket turned into a very large one and I have never seen any strong man among the people doing such a hard job. He pulled out so much water that the people (drank to
Grade: Sahih

Hadith #6761 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “While I was sleeping, I saw myself standing at a well over which there was a bucket. I pulled out from it as many buckets of water as Allah wished, and then Ibn Abi Quhafa (Abu Bakr) took the bucket from me and pulled out one or two full buckets, and there was weakness in his pull–may Allah forgive him. Then the bucket turned into a very large one and `Umar bin Al-Khattab took it. I have never seen any strong man among the people, drawing water with such stre
Grade: Sahih

Hadith #6762 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “While I was sleeping, I saw myself standing over a tank (well) giving water to the people to drink. Then Abu Bakr came to me and took the bucket from me in order to relieve me and he pulled out one or two full buckets, and there was weakness in his pulling –may Allah forgive him. Then Ibn Al-Khattab took it from him and went on drawing water till the people left (after being satisfied) while the tank was over flowing with water.”
Grade: Sahih

Hadith #6763 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
We were sitting with Allah’s Messenger (ﷺ), he said, “While I was sleeping, I saw myself in Paradise. Suddenly I saw a woman performing ablution beside a palace. I asked, “For whom is this palace?” They (the angels) replied, “It is for `Umar bin Al-Khattab.” Then I remembered `Umar’s ghira and went back hurriedly.” On hearing that, `Umar started weeping and said, ” Let my father and mother be sacrificed for you. O Allah’s Messenger (ﷺ)! How dare I think of my Ghira being
Grade: Sahih

Hadith #6764 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said: (I saw in a dream that) I entered Paradise, and behold, there was a palace built of gold! I asked, ‘For whom is this palace?’ They (the angels) replied, ‘For a man from the Quraish.’ ” The Prophet added, “O Ibn Al-Khattab! Nothing stopped me from entering it except your Ghira.” `Umar said, “How dare I think of my Ghira being offended by you, O Allah’s Messenger (ﷺ)?”
Grade: Sahih

Hadith #6765 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
We were sitting with Allah’s Messenger (ﷺ) he said, “While I was sleeping, I saw myself in Paradise, and behold, a woman was performing ablution by the side of a palace. I asked, ‘For whom is this palace?’ They replied, ‘For `Umar’ Then I remembered the Ghira of `Umar and returned immediately.” `Umar wept (on hearing that) and said, ” Let my father and mother be sacrificed for you, O Allah’s Messenger (ﷺ)! How dare I think of my Ghira being offended by you.’
Grade: Sahih

Hadith #6766 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “While I was sleeping, I saw myself performing the Tawaf of the Ka`ba. Behold, there I saw a whitish-red lank-haired man (holding himself) between two men with water dropping from his hair. I asked, ‘Who is this?’ The people replied, ‘He is the son of Mary.’ Then I turned my face to see another man with red complexion, big body, curly hair, and blind in the right eye which looked like a protruding out grape. I asked, ‘Who is he?’ They replied, ‘He
Grade: Sahih

Hadith #6767 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “While I was sleeping, I saw a bowl full of milk was brought to me and I drank of it (to my fill) till I noticed its wetness flowing (in my body). Then I gave the remaining of it to `Umar.” They asked, “O Allah’s Messenger (ﷺ)! What have you interpreted (about the dream)? He said, “(It is Religious) knowledge.” (See Hadith No. 134)
Grade: Sahih

Hadith #6768 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Men from the companions of Allah’s Messenger (ﷺ) used to see dreams during the lifetime of Allah’s Messenger (ﷺ) and they used to narrate those dreams to Allah’s Messenger (ﷺ). Allah’s Messenger (ﷺ) would interpret them as Allah wished. I was a young man and used to stay in the mosque before my wedlock. I said to myself, “If there were any good in myself, I too would see what these people see.” So when I went to bed one night, I said, “O Allah! If you see any good in me, sh
Grade: Sahih

Hadith #6769 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I was a young unmarried man during the lifetime of the Prophet. I used to sleep in the mosque. Anyone who had a dream, would narrate it to the Prophet. I said, “O Allah! If there is any good for me with You, then show me a dream so that Allah’s Messenger (ﷺ) may interpret it for me.” So I slept and saw (in a dream) two angels came to me and took me along with them, and they met another angel who said to me, “Don’t be afraid, you are a good man.” They took me towards the Fire, and b
Grade: Sahih

Hadith #6770 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “While I was sleeping, I saw that a cup full of milk was brought to me and I drank of it and gave the remaining of it to `Umar bin Al-Khattab.” They asked. What have you interpreted (about the dream)? O Allah’s Messenger (ﷺ)?” The Prophet (ﷺ) said. “(It is Religious) knowledge.”
Grade: Sahih

Hadith #6771 - Sahih al-Bukhari (Sahih al-Bukhari)
I asked Ibn Abbas about the dream of Allah’s Messenger which he mentioned. (see following hadith)
Grade: Sahih

Hadith #6772 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “While I was sleeping, two golden bangles were put in my two hands, so I got scared (frightened) and disliked it, but I was given permission to blow them off, and they flew away. I interpret it as a symbol of two liars who will appear.” ‘Ubaidullah said, “One of them was Al-`Ansi who was killed by Fairuz at Yemen and the other was Musailama (at Najd) .
Grade: Sahih

Hadith #6773 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I saw in a dream that I was migrating from Mecca to a land where there were date palm trees. I thought that it might be the land of Al-Yamama or Hajar, but behold, it turned out to be Yathrib (i.e. Medina). And I saw cows (being slaughtered) there, but the reward given by Allah is better (than worldly benefits). Behold, those cows proved to symbolize the believers (who were killed) on the Day (of the battle) of Uhud, and the good (which I saw in the dream) was the good
Grade: Sahih

Hadith #6774 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “We (Muslims) are the last (to come) but (will be) the foremost (on the Day of Resurrection).” Allah’s Messenger (ﷺ) further said, ”While sleeping, I was given the treasures of the world and two golden bangles were put in my hands, but I felt much annoyed, and those two bangles distressed me very much, but I was inspired that I should blow them off, so I blew them and they flew away. Then I interpreted that those two bangles were the liars between whom I
Grade: Sahih

Hadith #6775 - Sahih al-Bukhari - Abdullah bin (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I saw (in a dream) a black woman with unkempt hair going out of Medina and settling at Mahai’a, i.e., Al-Juhfa. I interpreted that as a symbol of epidemic of Medina being transferred to that place (Al-Juhfa).
Grade: Sahih

Hadith #6776 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
concerning the dream of the Prophet (ﷺ) in Medina: The Prophet (ﷺ) said, “I saw (in a dream) a black woman with unkempt hair going out of Medina and settling at Mahai’a. I interpreted that as (a symbol of) the epidemic of Medina being transferred to Mahai’a, namely, Al-Juhfa.”
Grade: Sahih

Hadith #6777 - Sahih al-Bukhari - Salim's father (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I saw (in a dream) a black woman with unkempt hair going out of Medina and settling in Mahai’a. I interpreted that as (a symbol of) epidemic of Medina being transferred to Mahai’a, namely, Al-Juhfa.”
Grade: Sahih

Hadith #6778 - Sahih al-Bukhari - Abu Musa al-Asha'ari (Sahih al-Bukhari)
The Prophet (ﷺ) said, “I saw in a dream that I waved a sword and it broke in the middle, and behold, that symbolized the casualties the believers suffered on the Day (of the battle) of Uhud. Then I waved the sword again, and it became better than it had ever been before, and behold, that symbolized the Conquest (of Mecca) which Allah brought about and the gathering of the believers. “
Grade: Sahih

Hadith #6779 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Whoever claims to have seen a dream which he did not see, will be ordered to make a knot between two barley grains which he will not be able to do; and if somebody listens to the talk of some people who do not like him (to listen) or they run away from him, then molten lead will be poured into his ears on the Day of Resurrection; and whoever makes a picture, will be punished on the Day of Resurrection and will be ordered to put a soul in that picture, which he will not
Grade: Sahih

Hadith #6780 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “The worst lie is that a person claims to have seen a dream which he has not seen.”
Grade: Sahih

Hadith #6781 - Sahih al-Bukhari - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف (Sahih al-Bukhari)
I used to see a dream which would make me sick till I heard Abu Qatada saying, “I too, used to see a dream which would make me sick till I heard the Prophet (ﷺ) saying, “A good dream is from Allah, so if anyone of you saw a dream which he liked, he should not tell it to anybody except to the one whom he loves, and if he saw a dream which he disliked, then he should seek refuge with Allah from its evil and from the evil of Satan, and spit three times (on his left) and should not tell it to
Grade: Sahih

Hadith #6782 - Sahih al-Bukhari - Abu Sa'id al-Khudri (Sahih al-Bukhari)
I heard Allah’s Messenger (ﷺ) saying, “If anyone of you saw a dream which he liked, then that was from Allah, and he should thank Allah for it and tell it to others; but if he saw something else, i.e, a dream which he did not like, then that is from Satan and he should seek refuge with Allah from it and should not tell it to anybody for it will not harm him.”
Grade: Sahih

Hadith #6783 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
A man came to Allah’s Messenger (ﷺ) and said, “I saw in a dream, a cloud having shade. Butter and honey were dropping from it and I saw the people gathering it in their hands, some gathering much and some a little. And behold, there was a rope extending from the earth to the sky, and I saw that you (the Prophet) held it and went up, and then another man held it and went up and (after that) another (third) held it and went up, and then after another (fourth) man held it, but it broke and th
Grade: Sahih

Hadith #6784 - Sahih al-Bukhari - Samra bin Jundub (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) very often used to ask his companions, “Did anyone of you see a dream?” So dreams would be narrated to him by those whom Allah wished to tell. One morning the Prophet (ﷺ) said, “Last night two persons came to me (in a dream) and woke me up and said to me, ‘Proceed!’ I set out with them and we came across a man lying down, and behold, another man was standing over his head, holding a big rock. Behold, he was throwing the rock at the man’s head, injuring it.
Grade: Sahih